Magnetic field interference on computer caused by three phase transmission lines / Mazelan Majid - Majid, Mazelan (1998)
Cabling structure design has been one of many aspects which has been taken with great care. A great deal of security precautions taken as to the placement of cables in big buildings which uses high voltage of electricity. Cabling structure has always been designed to fit in ceilings, at roofs or in hidden places. With such a design, magnetic field interference do exist for electrical equipments. In real, the Kuala Lumpur Stock Exchange (KLSE) is facing this difficulty whereby cable carrying current weight of 2KA is fixed at the ceiling of the computer room. Enormous Magnetic Field Interference causes the monitor displays to shake and blink. This actual phenomena brings about to the conduct of this entire project. The main objective is to experiment grounding effect and orientation. Details of experiment is explained deeply in the following chapters. Results are carefully tabulated and portrayed with 3D graphs plotted to show clearly how cabling design can affect the above phenomena which is still deemed to be a mystery. It is hoped that a general relationship is obtained between the level of magnetic field and current and the severeness of the screen problem. To the next extent possible, a way out to the problem is seeked.